Plastic rabbit runs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A rabbit raising cooperative in Martinique is experimenting with the use of light, plastic shelters for small livestock operations. Similar to temporary greenhouses, these plastic structures have numerous advantages for small producers with little...